Central antinociceptive and mechanism of action of pereskia bleo kunth leaves crude extract, fractions, and isolated compounds - Carolina Carvalho Guilhon; Ikarastika Rahayu Abdul Wahab; Fabio Boylan; Patricia Dias Fernandes (2015)
Pereskia bleo (Kunth) DC. (Cactaceae) is a plant commonly used in popular medicine in Malaysia. In this work, we evaluate the antinociceptive effect of P. bleo leaf extracts and isolated compounds in central antinociceptive model. Ethanol extract (E), hexane (H), ethyl acetate (EA), or butanol (B) fractions (30, 50, or 100 mg/kg, p.o.), sitosterol (from hexane) and vitexin (from ethyl acetate), were administered to mice. Antinociceptive effect was evaluated in the hot plate and capsaicin- or glutamate-induced licking models. Morphine (1 mg/kg, p.o.) was used as reference drug. Naloxone (1 mg/kg, i.p.), atropine (1 mg/kg, i.p.), and L-nitro arginine methyl ester (L-NAME, 3 mg/kg, i.p.) were administered 30 min earlier (100 mg/kg, p.o.) in order to evaluate the mechanism of the antinociceptive action. Higher dose of B developed an effect significantly superior to morphine-treated group. Naloxone prevented the antinociceptive effect of all fractions. L-NAME demonstrated effect against E, EA, and B. In all fractions, sitosterol and vitexin reduced the licking time after capsaicin injection. Glutamate-induced licking response was blocked by H, EA, and B. Our results indicate that Pereskia bleo fractions, sitosterol and vitexin, possessed a central antinociceptive effect. Part of this effect is mediated by opioid receptors and nitrergic pathway.